Communication Audit on the Internal Public of Kenya National Library Service (KNLS) - Ngugi, Nancy (Daystar University, School of Communication, 2004)
This study examined the effectiveness and adequacy of the existing internal communication systems used by Kenya National Library services (KNLS), in meeting the information needs of its employees. This was done in recognition of the fact that since its inception more than three decades ago, KNLS had never carried out any communication research. This meant that the communication system operating in KNLS then, were not based on or supported by any research. Yet, as an organization becomes more significant (Kumar, 1997, p.47). This study was therefore deemed necessary due to the various changes that KNLS had experienced over the years. The study was carried out in six of the then 33 KNLS branch libraries plus the headquarters. The six were purposively selected to capture the three KNLS library categories. Which were provincial, district, and community based libraries. The libraries studied were Nairobi and Nyeri in the provincial category, Meru and Thika in the district category. A questionnaire was self-administered to a purposefully deter- mined sample of 250 (72.5%) of the population study of 345 KNLS employees in the studied libraries. A response rate of 60.4% that is, 151 questionnaires, was realized. In addition, eight in-depth inter- views were conducted as a follow-up to issues raised by the question- naire data. The study indicated that the communication systems used by, KNLS did not adequately and effectively meet the information needs of its employees. For example, results showed that the amount of information received by the employees through various channels was much less than the amount they desired through the same channels. Similarly, the amount of information the employees received on various topics was significantly lower than the amount desired on the same topics.
Thesis
Keywords: internal communication systems; Kenya National Library services (KNLS)